DETERMINAN WASTE MANAGEMENT DISCLOSURE PADA PERUSAHAAN INDONESIA - Rizki, Tabah; Taufiq, Eindye (Worksheet : Jurnal Akuntansi, 2025)
This study aims to examine the effect of company size, profitability (ROA), proportion of female board of directors, and leverage on waste management disclosure in non-financial companies listed in Indonesia. Waste management disclosure is important to assess the extent to which companies are committed to sustainability and environmental social responsibility. This study uses secondary data from annual reports and sustainability reports of companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2023. The sample used amounted to 136 companies selected by purposive sampling method. The analytical tool used in this research is multiple linear regression which is processed using STATA statistical software. The regression analysis results show that ROA and female board of directors have a positive and significant effect on waste management disclosure. Companies with higher profitability, more female directors, and those operating in industries with greater environmental impact tend to provide better disclosures related to waste management. On the other hand, size and leverage do not have a significant influence on disclosure. These findings provide important implications for companies to pay more attention to factors that can encourage transparency in waste management disclosure, as well as for regulators to consider policies that can increase sustainability disclosure, especially in sectors that are more exposed to environmental impacts.